2015
DOI: 10.1016/j.joca.2015.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory biomarkers in osteoarthritis

Abstract: Summary Osteoarthritis (OA) is highly prevalent and a leading cause of disability worldwide. Despite the global burden of OA, diagnostic tests and treatments for the molecular or early subclinical stages are still not available for clinical use. In recent years, there has been a large shift in the understanding of OA as a “wear and tear” disease to an inflammatory disease. This has been demonstrated through various studies using MRI, ultrasound, histochemistry, and biomarkers. It would of great value to be abl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
92
1
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(106 citation statements)
references
References 115 publications
5
92
1
2
Order By: Relevance
“…The increase in lipid and protein levels may be attributed to the accumulation of lipids and total fatty acids (such as hypercholesterolaemia), and increased protein expression levels, which have been previously reported in OA . Other studies have shown that inflammatory mediators are increased in OA in comparison to healthy subjects, which can be reflected outside the joint tissues in blood plasma and peripheral blood leucocytes . Similar to a number of preceding studies demonstrating increased levels of collagen in OA subjects after analysing cartilage or blood samples, our results also showed a statistically significant increase of the collagen band (1034 cm −1 ) in OA (Fig ) .…”
Section: Discussionsupporting
confidence: 90%
“…The increase in lipid and protein levels may be attributed to the accumulation of lipids and total fatty acids (such as hypercholesterolaemia), and increased protein expression levels, which have been previously reported in OA . Other studies have shown that inflammatory mediators are increased in OA in comparison to healthy subjects, which can be reflected outside the joint tissues in blood plasma and peripheral blood leucocytes . Similar to a number of preceding studies demonstrating increased levels of collagen in OA subjects after analysing cartilage or blood samples, our results also showed a statistically significant increase of the collagen band (1034 cm −1 ) in OA (Fig ) .…”
Section: Discussionsupporting
confidence: 90%
“…In addition to epigenetic changes, it is also clear that chronic and low-grade inflammation is involved in the progression of OA (5356) that leads to catabolic responses in chondrocytes via upregulation of factors such as nuclear factor-kappa B (NF-κB) (57), MMPs, and markers of chondrocyte hypertrophy (e.g., Col10a1 , Mmp13 , Runx2 , Alp ). Recent investigations from human patients as well as animal models suggest that the entire synovial joint, including articular cartilage, subchondral bone, synovial tissue, ligament, and meniscus, contribute to the inflammation network.…”
Section: Epigenetic and Inflammatory Changes In Oamentioning
confidence: 99%
“…This in future could be a promising candidate to assess for association with OA Although previous studies have identified associations of pro-inflammatory cytokines with cartilage destruction, subchondral bone remodeling, synovial inflammation (7,11), and OA severity and progression (43)(44)(45), only a limited number of studies have reported correlations of sf IL-6, IL-8 and TNFα to levels of pain. As shown in animal studies, locally produced cytokines and chemokines can contribute to the sensitization of joint nociceptors (12), thereby identifying pro-inflammatory factors as etiologies of pain.…”
Section: Accepted Manuscriptmentioning
confidence: 99%